Urchin-Like Ni2/3Co1/3(CO3)1/2(OH)·0.11H2O for High-Performance Supercapacitors - Jiang, Zi-Min; Xu, Ting-Ting; Yan, Cong-Cong; Ma, Cai-Yun; Dai, Shu-Ge (Frontiers in Chemistry, 2018)
Here, we report our finding in the fabrication of novel porous Ni2/3Co1/3(CO3)1/2(OH)•0.11H2O (denoted as NC) electrode material with urchin-like structure composed of numerous nanoneedles through an one-step hydrothermal method, which delivered a high specific capacity of 318 C g-1 at a current density of 1 A g-1. Moreover, an architectural composite electrode consisting of the porous NC nanoneedles wrapped by reduced graphene oxide (rGO) nanosheets exhibits large specific capacity (431 C g-1 at 1 A g-1), high rate capability and long cycling life (94% capacity retention after 5000 cycles at 20 A g-1). The presence of rGO in the composite electrode greatly improves the electronic conductivity, providing efficient current collection for fast energy storage.